Training And Recognition of The Importance of Cybersecurity For Umkm In Entering The Digital Market - Yusnanto , Tri (Institute of Education and Social Research, 2023)
Borobudur district is a district located in Magelang district with 20 districts. Dusun Ngaran I is one of the dunes in Borobudur, with a number of UMKM perpetrators more than 15 UMKM. Asoy Warung UMKM is a UMKM in Dusun ngaran I that shakes in the field of processing of soy milk snakes. UMKM itself is a productive enterprise that is considered by individuals or enterprises that have met the criteria as a micro enterprise. The Covid-19 pandemic encourages UMKM to conduct business activities through digital platforms. So UMKM becomes a potential target for cyber security attacks. Lack of education and introduction to cyber security, many UMKM perpetrators are not aware of the threat of cyberattacks.The urgency of this activity is that the attacks targeting UMKM indirectly are the effect of the Covid-19 pandemic that requires to shift the process of transactions mainly sales and sales and promotions using digital media and the Internet. The education and training provided is to recognize digital assets, security defence updates, password management, threats of phishing and malware attacks as well as backup and data recovery. The objective of this activity is to provide training training and recognition of the importance of cyber capabilities for UMKM in entering the digital market. The methods carried out are training and support to know the digital asset and the application of the basics of cybersecurity in preventing cyber attacks.